Beyond Words: Breaking the Boundaries of Legal Language - Ohana, Natalie (feminists@law, 2016)
This is the transcript of a Tedx talk given at Goodenough College, London on 21 May 2016. The author describes an art and dialogue workshop she conducted with artist Dr Sue Challis at a women’s refuge in London run by Solace Women’s Aid. The art works produced by women residing in the refuge concerning encounters with the legal system prompted reflections on the limits of language – especially legal language – as a tool to convey painful and traumatic experiences, and the value of combining language and art as a more effective means for expression and communication. A video of the talk is available at https://m.youtube.com/watch?v=-Ydrf7DljfQ.